Steep Declines in Pediatric AIDS Mortality in South Africa, Despite Poor Progress Toward Pediatric Diagnosis and Treatment Targets - Johnson, Leigh F; Patrick, Mark; Stephen, Cindy; Patten, Gabriela; Dorrington, Rob E; Maskew, Mhairi; Jamieson, Lise; Davies, Mary-Ann (The Pediatric infectious disease journal, 2020)
Few attempts have been made to monitor progress toward HIV diagnosis and antiretroviral treatment (ART) coverage targets in children, and the impact that ART and prevention of mother-to-child transmission (PMTCT) programs have had on pediatric HIV incidence and mortality. A multiparameter evidence synthesis approach was adopted to integrate South African pediatric HIV data sources. A previously developed model of HIV in South Africa was calibrated to household survey HIV prevalence data, routine antibody testing data, data on numbers and ages of children on ART, vital registration data and data on HIV diagnosis at death. The impact of ART and PMTCT was estimated by comparing validated model outputs against model predictions of the trends that would have been expected in the absence of ART and PMTCT. By mid-2018, the model estimated that 75.2% (95% CI: 73.9%-76.8%) of HIV-positive children were diagnosed, substantially lower than the corresponding estimates in HIV-positive adults (91.0%). ART coverage in children in 2018 (51.2%, 95% CI: 49.4%-52.7%) was also lower than that in adults (62.0%). In 2017-2018, the numbers of new cases of mother-to-child transmission and pediatric AIDS deaths were reduced by 84% and 94%, respectively, relative to what would have been expected in the absence of interventions, but reductions in mortality were driven largely by PMTCT. Although levels of AIDS mortality in children have declined dramatically in South Africa, this has mostly been due to successful PMTCT programs, and progress toward the 90-90-90 targets appears relatively poor when compared with that in adults.